The Association Between Hypospadias Occurrence With Exposure Of Pesticides In Agroindustry Enviroment - Sri Weli Teguh Pujo Sakti; Supangat Supangat; Septa Surya Wahyudi (Faculty of Nursing, Universitas Jember, 2018)
Hypospadias is congenital penis abnormalities in children who are commonly encountered. Structure of the urinary tract is found in the central part of the penis. Many factors cause the occurrence of hypospadias, one of which is exposure to pesticides. Indonesian’s people have a livelihood as farmers, hence the case of contaminated pesticides often occur in the agroindustrial environment. The type of this research is analytic observational by a case-control method which conducted in November until December 2017. The criteria in this study were all hypospadias patients and had undergone treatment at Paru Hospital of Jember, Bina Sehat Hospital of Jember, Bhayangkara Hospital of Bondowoso from January 2015 until November 2017 and close community of patient in one agroindustry region. The sample of this research is 40 samples divides into 20 sample case groups and 20 sample control groups. The data obtained were analyzed by Chi-square test and obtained significant result between the employment relationship (p = 0.011) and pesticide exposure with categories pesticide user (p = 0.026), spacing distance with mother position (p = 0.011), pesticide contact time (p = 0.004), pesticide storage area (p = 0.001) to hypospadias occurrence in the agroindustry environment.